Píla í sveitinni - Robyn Elizabeth Vilhjálmsson 1956- (2012)
b) Píla í sveitinni is a children´s book intended for a three- to six-year old audience. The main character is a sheep-dog named Píla. She meets sheep, horses, cows and reindeer, learns about them, where they live and how they spend their lives. This essay discusses the book and fits it into the history of Icelandic children´s literature. Animals play an important role in children´s literature but it is also it is asked how children see real animals and nature. The Playschool Curriculum, 2011 is examined in relation to its emphasis on the concepts of the environment and sustainability, and whether the children´s book as a medium can teach these concepts. Various theories of children´s cognitive development are examined to show that young children actively seek after the familiar, local and domestic rather than the exotic, regional and unfamiliar. The social interaction between children and animals is discussed with special emphasis on caring as a theme. It is questioned whether the concept of caring can be extended to the wider environment and if this is an appropriate method for teaching preschoolers about the environment and sustainability. Some of the environmental ideas in Píla í sveitinni may seem advanced cognitively for preschool children to grasp and so it is the role of the playschool teacher to interpret them in an age-appropriate manner. Although preschoolers learn mostly through direct experiences of nature, the children´s book can be a catalyst for play and an arena for discussion. Vocabulary skills and social development are benefits if the book is read in an interactive manner. Participatory research in Iceland, of a limited nature, shows preschoolers know little about animals. This was contrary to theory-based expectations. a) Píla í sveitinni er barnabók ætluð þriggja til sex ára leikskólabörnum. Aðalpersóna í bókinni er fjárhundur, Píla að nafni. Hún kemst í kynni við kindur, hesta, kýr og hreindýr og í gegnum hana er lært um dýrin, húsakynni og lífshætti þeirra. Fjallað er um sögu barnabóka ...